The Neolithic settlement of Aknashen (Ararat Valley, Armenia) : excavation seasons 2004-2015 - Badalian, Rouben S.; Chataigner, Christine; Harutʻyunyan, Armine (Archaeopress Archaeology, 2022)
The Neolithic settlement of Aknashen (Ararat valley, Armenia): excavation seasons 2004-2015 presents research based on an Armenian-French project, in which specialists from Canada, Romania, Germany and Greece also participated. The volume concerns the natural environment, material culture and subsistence economy of the populations of the first half of the 6th millennium BC, who established the first sedentary settlements in the alluvial plain of the Araxes river. The thickness of the cultural layer of Aknashen (almost 5m), the extent of the excavated areas and the multidisciplinary nature of the research, confer great importance upon this site for the study of the Neolithic, both in Armenia and in the South Caucasus as a whole.